Conjugate propagator method for direction finding - LIU Jian1; WANG Yan-wei1; HUANG Zhi-tao2; ZHOU Yi-yu2 (Tongxin xuebao)
A new direction finding algorithm called conjugate propagator method （COP） for one-dimension signals was proposed. The new algorithm uses the array output and its conjugate form to extend the array aperture so that it can detect more signals than sensors and has better performance （in terms of resolution and angular precision） than OPM （or-thonormal-PM） and MUSIC algorithms. The mean square error （MSE） performance of COP was analyzed and the ana-lytical expression of MSE was given. The computational complexity of COP was analyzed also. Simulation results show the better performance of COP than OPM and MUSIC algorithms and the accordance between the theoretical results and the simulation results.